Leukocyte CH25H is a potential diagnostic and prognostic marker for lung adenocarcinoma - Jun Zhang; Lidong Xu; Jun Gao; Jieyi Li; Xiaokai Zhao; Pengmin Yang; Yujun Ge; Dawei Guo; Zhonghua Liu; Xiyong Wang; Wenchao Gu; Pengli Wang; et al. (Scientific Reports, 2022)
Abstract Metastasis, a major challenge during the treatment of lung cancer, causes deterioration in patient health outcomes. Thus, to address this problem, this study aimed to explore the role and contribution of Cholesterol 25-Hydroxylase (CH25H) as a potential diagnostic and prognostic marker in lung cancer. Online public databases were used to analyze the expression level, prognostic value, gene-pathway enrichment, and immune infiltration of CH25H in lung cancer patients. The Real-Time Quantitative Reverse Transcription PCR (qRT-PCR) was used to analyze and detect the CH25H expression levels in leukocytes from lung cancer patients. The expression level of CH25H was significantly reduced in lung adenocarcinoma (LUAD), which is associated with a higher disease stage, but not in lung squamous cell carcinoma (LUSC). Kaplan–Meier survival analysis indicated that LUAD patients with low CH25H expression had a worse prognosis. Mechanistically, our results showed that in LUAD, CH25H may be a regulatory factor affecting the immune cell infiltration level, and the resultant tumor development. Experimental data showed that low expression of CH25H in leukocytes was significantly associated with LUAD metastasis (P < 0.01). Our study suggests that CH25H may function as a prognostic and risk stratification biomarker for LUAD.